Mediating effect of sleep quality on the association between job stress and health-related productivity loss among workers in R&D enterprises in Shanghai - Sun, Yixuan; Wei, Minqi; Zhao, Qiuwen; Yang, Jinfeng; Gao, Junling; Dai, Junming (Frontiers in Public Health, 2024)
Background: Past research indicates that occupational stress negatively predicts health-related productivity. Simultaneously, sleep problem among workers may stem from job stress, subsequently leading to a decline in sleep quality and resulting in reduced health productivity. Therefore, this study aims to idenitify whether the sleep quality of employees functions as a mediator in the process through which job stress impacts health productivity. Objectives: this study aimed to assess the status and analyze differences in quality of sleep, job stress, and health-related productivity loss (HRPL) among workers in research and development (R&D) enterprises in Minhang District, Shanghai. We also assessed the mediating effect of sleep quality on the relationship between job stress and HRPL. Methods: A total of 3,216 workers in R&D firms aged between 18 and 60 years participated in this study (mean age 35.15 years; standard deviation 8.44; male-to-female ratio≈2:1). The Nakata Insomnia Questionnaire, the Chinese version of the Brief Job Stress Questionnaire revised edition, and the Chinese version of the Work Productivity and Activity Impairment Questionnaire were used in this study. And the Kruskal-Wallis test, Hierarchical Multiple Regression Analysis, and Path Analysis were utilized for data analysis in this study. Results: There were significant differences in the positive detection rate of insomnia among participants according to age, educational level, marital status, position, length of service, and level of financial difficulties (all P<0.05). We also found significant differences in the positive detection rate of HRPL among participants according to age, marital status, length of service, and level of financial difficulties (all P<0.05); participants with insomnia scored higher for HRPL than those without insomnia (6.00 vs. 4.20, P<0.001). Additionally, participants with job stress problems had higher HRPL than those without these issues (7.00 vs. 4.20, P<0.001). Our findings suggest that sleep quality plays a mediating role between job stress and HRPL (all P<0.05). Conclusions: Occupational health professionals must pay particular attention to job stress, sleep quality, and their influencing factors to positively influence the wellbeing of workers while improving productivity.